2003
DOI: 10.14411/eje.2003.001
|View full text |Cite
|
Sign up to set email alerts
|

Searching and reproductive behaviour of female aphidophagous ladybirds (Coleoptera: Coccinellidae): a review

Abstract: Abstract. In searching both for food to produce eggs and for suitable oviposition sites, females of aphidophagous ladybirds must be adapted to exploit prey that vary greatly in their occurrence and abundance over both space and time. A simple model of ladybird searching and oviposition behaviour emerged in the 1950s: adult ladybirds are highly mobile in traversing the landscape, but become less active and produce more eggs as their rate of aphid consumption increases. The net result is that most eggs tend to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 87 publications
2
80
0
6
Order By: Relevance
“…The low number of beetles recaptured may be an artifact of the sampling method (i.e., nets do not collect all individuals in an area), but also may indicate that many ladybirds could have rapidly abandoned the landscapes. In fact, it has been described that ladybirds often do not remain long in any given location, but instead appear to move frequently between sites and habitats throughout the breeding season (Evans, 2003). Anyway, our data help develop an understanding of the dispersal behaviour of ladybirds that remain in the landscape, and may be useful for modelling the influence of dispersal on the abundance and distribution of coccinellids in fragmented landscapes (Tischendorf et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…The low number of beetles recaptured may be an artifact of the sampling method (i.e., nets do not collect all individuals in an area), but also may indicate that many ladybirds could have rapidly abandoned the landscapes. In fact, it has been described that ladybirds often do not remain long in any given location, but instead appear to move frequently between sites and habitats throughout the breeding season (Evans, 2003). Anyway, our data help develop an understanding of the dispersal behaviour of ladybirds that remain in the landscape, and may be useful for modelling the influence of dispersal on the abundance and distribution of coccinellids in fragmented landscapes (Tischendorf et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
“…Van der Werf et al (2000) observed increased residence time and 10-20 times higher abundance of lady beetles in sugar sprayed plots when compared with control plots. As the emigration rate is inversely proportional to the staying time, these works (reviewed in Evans, 2003) provide solid evidence that emigration rate decreases with increasing number of prey. Cardinale et al (2006) observed a linear negative relationship between the emigration rate of lady beetles and the logarithm of aphid density.…”
Section: Introductionmentioning
confidence: 92%
“…Aphidophagous ladybeetles (Coleoptera: Coccinellidae), as well as lacewings (Neuroptera: Chrysopidae) and hoverfl ies (Diptera: Syrphidae), the larvae of which prey on aphids, were identifi ed to species using identifi cation keys in San Martin (2004), van Veen (2010 and Roy et al (2013), respectively. Because the adults of these predatory families are all highly mobile and able to traverse agricultural landscapes (Evans, 2003;Villenave et al, 2006;Almohamad et al, 2009), their dispersion through the different plots was comparable.…”
Section: Monitoring Of Insect Speciesmentioning
confidence: 99%